Implementation of the Project Citizen Learning Model in Improving PPKn Learning Achievement at SMK Negeri 2 Salatiga - Endang Wahyuningsih (CV. Rayyan Dwi Bharata, 2002)
Teachers as educators have not been optimal in developing the creativity and innovative power of students, besides that teachers also still use conventional learning with the lecture method, resulting in low learning achievement from students. Therefore, a learning model is needed that can be used to improve student learning achievement. One model that can be used is the project citizen model. The method used is Class Action Research with qualitative and quantitative approaches. Data collection techniques use test guidelines, observation, and documentation. The findings in this study are that the implementation of the project citizen model in PPKn subjects can increase student learning achievement. This is shown by looking at the results of the initial conditions, cycle 1 to cycle 2 as the final stage of the classroom action research process. The average value in the initial condition is 70.28 and the average value in the final condition or cycle 2 is 83.28 with a significant increase of 18.49%.